Particle mobility and metabasin exploration in model glass-formers. - Appignanesi, Gustavo Adrian (2007)
In this work, we assess the relevance of different range particle displacements and string motions to the metabasin (MB) dynamics of a simple glass former. We find that MB transitions are triggered by the occurrence of massive rearrangements termed as "democratic clusters" or d-clusters which last on average less than 1% of the α-relaxation time. Thus, at variance from previous investigations that focused on large displacements and strings, our work points to the essential role of medium-range particle displacements: we find that d-clusters are compact objects since the local neighborhoods of the most mobile particles exhibit significant rearrangements with a clear prevalence of medium-range displacements (of around 20% of the interparticle distance). This is in contrast to the string-like movements for which we demonstrate that many of them fully develop in isolation (their local environment being mostly insensitive to them) and at times different from that of MB transitions, being thus irrelevant to the α-relaxation. Additionally, from the analysis of the MB dynamics, preliminary support to the dynamics facilitation scenario is provided.